(untitled) (Nepalese Journal of Management Research, 2024)
This study aims to analyze the impact of workforce diversity and employee performance of Standard Chartered Bank Nepal Limited. The study is quantitative in nature which is based on cross sectional research design. Data were collected from 200 bankers through primary survey. The findings reveal that gender, ethnicity and education diversity does not significantly impact employee performance which indicates that despite having diverse workforce in terms of gender, ethnicity and education does not differ in the employees’ performance of Standard Chartered. Rather it was found that age and experience has a significant positive impact on employee performance which implies that with diverse age group and experience in the organization tends employee to perform better. The outcomes of this study is useful to develop effective diversity management strategies that enhance employee performance, job satisfaction, and overall organizational success.